A protocol to reduce police wait times in the emergency department. Issue 4 (July 2015) - Pizzingrilli, Barb; Hoffman, Ron; Hirdes, Daniel Pearson
Healthcare organizations are increasingly tasked with implementing change initiatives that improve the patient experience and target priorities such as Emergency Department (ED) volumes. This article describes the development, implementation, and outcomes of a collaborative protocol between the Niagara Health System and the Niagara Regional Police Service that resulted in a 57% reduction in police wait times in the ED. Six critical success factors contributed to the outcomes that were achieved and are detailed for those organizations interested in engaging in a similar change initiative.